A Derrida reader : between the blinds - Derrida, Jacques (Harvester Wheatsheaf, 1991)
In the English-speaking world, Jacques Derrida’s writings have most influenced the discipline of literary studies. Yet what has emerged since the initial phase of Derrida’s influence on the study of English literature, classed under the rubric of deconstruction, has often been disowned by Derrida. What, then, can Derrida teach us about literary language, about the rhetoric of literature, and about questions concerning style, form, and structure?